If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -24 = 3 Reorder the terms: -24 + 3x = 3 Solving -24 + 3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 3x = 3 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 3 + 24 3x = 3 + 24 Combine like terms: 3 + 24 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| y=19/3/2x/3 | | 6x+3(4+6x)=2x+2(5x+6) | | 10-3x=x-2 | | x^2+4x+8y-44=0 | | 6h^2+3=0 | | 6x=9/10 | | 2*x-6=10 | | -301/10x-27 | | 9.40=x/1.65-x | | 5=7-z | | x^2-8x+4x-32=20 | | 10-6(3+10b)= | | 2w+3x= | | 7x+32+6x=9x+3x-62 | | 100=-16t^2+192t+30 | | 3x+140=400 | | 2w=3x | | 44.88=3.4(-3.4n+3) | | 3/4x=3/8(x-5)=1/4 | | 6x^2=20x-6 | | 10(-8+8n)-8= | | 11+10(p-10)=44+5(2p-11) | | 27b+(-4)=-814 | | 600+-4.5y+2y=425 | | 2y^2-7y+8y^2-6y= | | 27(w-972)=297 | | 2x-(18/x)=0 | | -4(3-5x)-4x= | | 63=9(d-84) | | z/8+73=82 | | 7x-3=(3/4(8x-12)) | | 5/x=11.3 |